UMP formed partnerships with us universities to reinforce its engineering technology programme - Emma Melati, Buhanuddin (Pejabat Naib Canselor, 2016)
Universiti Malaysia Pahang (UMP) formed collaborations with three universities in the United State (US) to further strengthen its technology engineering programme.